The Intention of Adopting Information Technology for SMES in Special Region of Yogyakarta - Wijaya, Tony; Budiman, Santi (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2019)
This study aims to examine the intention of adopting information technology for SMEs in DIY through the expansion of the technology acceptance model. This research continues the previous research related to aspects of obstacles experienced in the development of SME businesses. The research conducted a survey using a sample of SMEs entrepreneurs in DIY. The data analysis technique in this study uses structural equation models that are assisted by the AMOS program. Overall, the expansion model of the technology acceptance model in predicting the intention of adopting SME’s information technology in this study fulfils the model fit rules, which means that the model developed in this study is by existing empirical conditions. In particular, the results of the study prove the influence of business competition pressure on the usefulness of SME owners. It also found that ease of use and perceived usefulness have an effect on the attitudes towards SMEs information technology adoption of SMEs owners, and the attitudes on the adoption of SMEs information technology affect the intention of adopting SME’s information technology.